Risk stratification of individuals with low-risk colorectal adenomas using clinical characteristics: a pooled analysis - Gupta,S; Jacobs,ET; Baron,JA; Lieberman,DA; Murphy,G; Ladabaum,U; Cross,AJ; Jover,R; Liu,L; Martinez,ME (Gut, 2015)
OBJECTIVE: For individuals with 1-2 small (<1cm) low-risk colorectal adenomas, international guidelines range from no surveillance to offering surveillance colonoscopy in 5-10years. We hypothesised that the risks for metachronous advanced neoplasia (AN) among patients with low-risk adenomas differ based on clinical factors distinct from those currently used. DESIGN: We pooled data from seven prospective studies to assess the risk of metachronous AN. Two groups with 1-2 small adenomas were defined based on guidelines from the UK (n=4516) or the European Union (EU)/US (n=2477). RESULTS: Absolute risk of metachronous AN ranged from a low of 2.9% to a high of 12.2%, depending on specific risk factor and guideline used. For the UK group, the highest absolute risks for metachronous AN were found among individuals with a history of prior polyp (12.2%), villous histology (12.2%), age ≥70years (10.9%), high-grade dysplasia (10.9%), any proximal adenoma (10.2%), distal and proximal adenoma (10.8%) or two adenomas (10.1%). For the EU/US group, the highest absolute risks for metachronous AN were among individuals with a history of prior polyp (11.5%) or the presence of both proximal and distal adenomas (11.0%). In multivariate analyses, strong associations for increasing age and history of prior polyps and odds of metachronous AN were observed, whereas more modest associations were shown for baseline proximal adenomas and those with villous features. CONCLUSIONS: Risks of metachronous AN among individuals with 1-2 small adenomas vary according to readily available clinical characteristics. These characteristics may be considered for recommending colonoscopy surveillance and require further investigation.